Arsenic speciation in fish and shellfish from the North Sea (Southern bight) and Açu Port area (Brazil) and health risks related to seafood consumption. (January 2018) - Gao, Yue; Baisch, Paulo; Mirlean, Nicolai; Rodrigues da Silva Júnior, Flavio Manoel; Van Larebeke, Nik; Baeyens, Willy; Leermakers, Martine
Abstract: In North Sea and Port Açu (Brazil) coastal areas, high arsenic (As) concentrations were observed in water, soil and sediments. Therefore, the impact of this contamination on fish and shellfish species bought from local fishermen was studied. Total As was assessed with ICP-OES (Brazil) and ICP-MS (North Sea) after microwave digestion. Toxic As was assessed with liquid chromatography-ICP-MS (Brazil) and hydride generation-atomic fluorescence spectrometry (North Sea). All analytical methods comply with Quality Assurance/Quality Control procedures. Several fish species have average Total As concentrations above 1 μg g-1 wet weight (ww), but the highest concentrations are found in less spotted dogfish, lemon sole and whelks from the North Sea, with respectively 50, 49 and 50 μg g-1 ww. High Total As concentrations correspond to high Toxic As concentrations, except for scallops having increased Toxic As concentrations. Toxic As fractions are highest in scallops (almost 10%) but rarely exceeds 2% in all other species. Liver samples were only analyzed in ray, dogfish and catfish and their Toxic As fractions are between 2 and 4 times higher than in muscle. For a consumption of 150 g of seafood, only 3 samples exceed the provisional total daily intake of 2 μg kg-1 bw, however, cancer risks are non-negligible. Using mean Toxic As concentrations for each of the different fish and shellfish species studied, Lifetime Cancer Risk values at the actual global seafood consumption rate of 54 g day-1 are above 10–4 for whelks, scallops, dogfish, ray and lemon sole. Graphical abstract: Image 1